MORPHOLOGICAL ASPECTS OF CONGENITAL AND ACQUIRED HEART DEFECTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Heart defects remain one of the most significant causes of cardiovascular pathology and population disability, occupying a leading position in the structure of congenital and acquired heart diseases. Despite significant advances in clinical cardiology and cardiac surgery, the morphological aspects of the formation and progression of heart defects continue to be of high scientific interest. The development of heart defects is based on disturbances of embryogenesis, remodeling of the myocardium and valvular apparatus, as well as changes in the microcirculatory bed and extracellular matrix. Morphological remodeling includes hypertrophy and dilation of cardiac chambers, fibrosis, disorganization of cardiomyocytes, and alterations in the structure of the endocardium and valves. The aim of this review is to analyze current literature data on the morphological features of congenital and acquired heart defects, with an emphasis on histological and ultrastructural changes of the myocardium and valvular apparatus. The presented data emphasize the significance of morphological studies for understanding the pathogenesis of heart defects and for substantiating new diagnostic and therapeutic approaches.